PONDER for Specifying the Policies of Multimedia Sessions Management - Sekkaki, A.; El Hamzaoui, M.; Bensassi, B.; Westphall, C. B.; Westphall, C. M. (INFOCOMP Journal of Computer Science, 2007)
Distributed multimedia systems allow a group of persons to see each other, communicate and work together on shared resources independently on their geographical positions. The multimedia systems rest on session concept to organize users in well defined groups. Many works realized inside the IETF (Internet Engineering Task Force) are devoted to the standardization of description, annoncement and initiation of the multimedia sessions on Internet. However, the problem of coordination within multimedia sessions is not dealt with in these works. In this paper, we will use the policy-based management to manage automatically the coordination inside teleconference systems sessions that belongs to multimedia distributed systems. Our approach is based exactly on the policies specification language Ponder to specify policies designed to manage the intra-session coordination